Clusters, social networks and marketing collaboration in small firms: exploratory evidence from Chile and Scotland. (3rd June 2008) - Felzensztein, Christian
This research studies the factors that influence the development of marketing externalities among cluster based small firms. Theorists have consistently demonstrated the role and importance of economic externalities. Less research attention has been paid to the investigation of marketing-based externalities, though it has been suggested that these may also accrue from geographical agglomeration. This study explores the development of joint marketing activities and alliances between small firms operating in the salmon farming industry in Chile and Scotland. The results suggest that social networking has a greater influence than geographic proximity in facilitating interfirm cooperation in marketing activities. The study also found that few differences could be attributed to a prevailing national culture; however, specific regional economies within countries may have specific characteristics that affect cooperative behaviour and which may differ from those found within the country's general context.